Controlled Electrodeposition and Magnetic Properties of Co35Fe65 Nanowires with High Saturation Magnetization. Issue 2 (1st January 2017) - Ghemes, Adrian; Dragos-Pinzaru, Oana; Chiriac, Horia; Lupu, Nicoleta; Grigoras, Marian; Shore, Daniel; Stadler, Bethanie; Tabakovic, Ibro
Abstract : Among all transition metals magnetic alloys, Co35 Fe65 possesses the highest saturation magnetization BS = 2.45 T at room temperature given by the so-called "Slater-Pauling limit". For controlled electrodeposition of Co35 Fe65 nanowire arrays the following parameters were found to be optimal: electrolyte solution with 1–2 mM malonic acid (MA), ionic ratio Fe +2 /Co +2 = 2.0, growth rate, and pulsed potential deposition with time-on (2.5 s) at the potential of −1.15 V/SCE and time-off (1.0 s) at −0.70 V/SCE. These arrays were deposited inside anodic aluminum oxide (AAO) templates that contained columnar nanopores with diameters either 35 or 200 nm. Cyclic voltammetry was used in solution with and without MA and reaction mechanism was proposed to explain the critical role of MA in electrodeposition of CoFe alloys. In addition to uniform deposition of stechiometric Co35 Fe65 alloys, a selectivity ratio, (SR) ∼1.0, were achieved, which means that the atomic ratio of Fe/Co in the nanowire matched the molar ratio of Fe +2 /Co +2 in the electrolyte. The magnetic behavior of the subsequent 2.45 T Co35 Fe65 nanowire arrays showed that the shape and magnetostatic anisotropies dominated the effective anisotropy, and the impact of magnetocrystalline and magnetelastic anisotropies field was very small.